2016
DOI: 10.1017/s1047951116000561
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancy in a Fontan-palliated patient

Abstract: The Fontan connection, originally described in 1971, is used to provide palliation for patients with many forms of CHDs that cannot support a biventricular circulation. An increasing number of females who have undergone these connections in childhood are now surviving into adulthood and some are becoming pregnant. We report a case of a 29-year-old woman who presented with a twin pregnancy at 33 weeks of gestation. She had significant deterioration of her cardiovascular status before the twin babies were delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Only 4 cases of twin pregnancies in women with a Fontan circulation have been reported. Among the 4 cases, 2 were described in detail as case reports [ 11 , 12 ], and 2 were included in research articles where detailed information on clinical course was lacking [ 1 , 4 ]. In a case reported by Nair et al, the patient had significant deterioration in cardiovascular function at 33 weeks' gestation, necessitating emergency cesarean section [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 cases of twin pregnancies in women with a Fontan circulation have been reported. Among the 4 cases, 2 were described in detail as case reports [ 11 , 12 ], and 2 were included in research articles where detailed information on clinical course was lacking [ 1 , 4 ]. In a case reported by Nair et al, the patient had significant deterioration in cardiovascular function at 33 weeks' gestation, necessitating emergency cesarean section [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 4 cases, 2 were described in detail as case reports [ 11 , 12 ], and 2 were included in research articles where detailed information on clinical course was lacking [ 1 , 4 ]. In a case reported by Nair et al, the patient had significant deterioration in cardiovascular function at 33 weeks' gestation, necessitating emergency cesarean section [ 11 ]. Nir et al reported a case involving a patient who complained of shortness of breath after climbing two flights of stairs (functional class II) at 30 weeks' gestation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%